THE COMPARATIVE STUDY OF THE NOVEL AND THE FILM OF HARRY POTTER “THE DEATHLY HALLOWS” - Adjie, Dwi Nova; nopriansah, nopriansah (JURNAL LITERARY CRITICISM, 2018)
This thesis studied about Comparative Study of Novel and Film of Harry Potter The Deathly Hallows. The objectives of this research are to find out the similarities data and the differences data in intrinsic elements of both literary works. This research used theory of  Eneste (1991) to analysis the reduction, addition, and modification in ecranisation study. This research used descriptive qualitative, the data collected from the intrinsic elements of novel and film. In collecting data, the researcher used note taking as the instrument to find out the reduction, addition, and modification of novel into film. In this research, the researcher found that there were 15.49% in plot data, in character 62.97% data, in setting 19.71% data and point of view 2.81% data or 76.34% in total data was similar. While in differences there are 22 data separated in reduction 63.63% data, in addition 23.27%% data and in modification 13.63% data was found. In addition, the researcher found that reduction, addition and modification influenced to the change of some intrinsic elements in both of fiction.   Keywords: Comparative Study, Novel, Film, Ecranisation.